Are school factors and urbanization supportive for being physically active and engaging in less screen-based activities - Kopcakova, Jaroslava; Dankulincova Veselska, Zuzana; Madarasova Geckova, Andrea; Klein, Daniel; van Dijk, Jitse P; Reijneveld, Sijmen A (International journal of public health, 2018)
OBJECTIVES: The aim was to assess the association between physical activity and screen-based activities in adolescents and selected school factors and urbanization and whether these associations were modified by degree of urbanization. METHODS: We obtained data regarding the fifth-ninth grade students from 130 schools in 2014 via the Health Behaviour in School-aged Children cross-sectional study in Slovakia (n = 9743, mean age = 13.5, 50.3% boys). We explored the associations using multilevel logistic regression. RESULTS: We found significant associations between physical activity and the accessibility of an area for skating/tennis court [odds ratio (OR) = 1.20 and 95% confidence interval (CI) 1.01-1.42], and between physical activity and active breaks (OR = 0.83 and 95% CI 0.69-0.99). The rates of screen-based activities were higher in small towns (OR = 1.63, 95% CI 1.29-2.06), towns (OR = 1.30, 95% CI 1.08-1.57), and cities (OR = 1.40, 95% CI 1.04-1.87) than in villages. CONCLUSIONS: School environment and degree of urbanization are associated with adolescents' physical activity and screen-based activities. This holds positively for access to an area for skating/tennis court and negatively for active breaks regarding physical activity and for living in villages regarding less use of screens.
Keywords: Odds Ratio; lidé; mladiství; velkoměsta; cvičení; odds ratio; Slovakia; Female; Public Facilities; dítě; Exercise; Schools; Environment; Adolescent; Humans; Urbanization; urbanizace; průřezové studie; školy; Slovenská republika; Cross-Sectional Studies; životní prostředí; Cities; logistické modely; mužské pohlaví; Sedentary Behavior; ženské pohlaví; Logistic Models; Male; veřejná zařízení; Child; sedavý životní styl